LASIK surgery in children. Issue 1 (23rd December 2003) - O'Keefe, M; Nolan, L
Abstract : Aims: To report success in the treatment of high myopia in children with LASIK. To report the visual results, complications and postoperative management of children with high myopia. Methods: Six children (seven eyes) with high myopia were included in this series. Preoperative and postoperative refraction, visual acuity, and pachymetry were compared. Results: Six children with high myopia ranging from −5.00DS to −16DS were treated. There were three males and three females. Five children had improved refraction and visual acuity post-LASIK. Age ranged from 2 to 12 years. Five of the children had unilateral amblyopia preoperatively. One had bilateral high myopia. Conclusion: High myopia in children may be treated safely and effectively with LASIK.